2017
DOI: 10.1002/suco.201600169
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on frame structures with recycled aggregate concrete under lateral cyclic loads

Abstract: This paper presents an experimental study on the seismic behavior of frame structures made with recycled aggregate concrete (RAC). Three 1:2 scaled frame specimens were tested under lateral cyclic loads and constant vertical load. One of these frames was conventional concrete frame, while the remaining two frames were RAC frames with a recycled coarse aggregate (RCA) replacement percentage of 25 and 50%, respectively. The structural performances, in terms of the failure pattern and mechanism, ultimate lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A large number of researches have been conducted on the fresh, mechanical properties and durability of recycled concrete at national and international. Many studies have shown that RCA can be used as building materials, such as graded slabs, 6 beams, 7 frame structures, 8 highway cushion material, 9 paving blocks, 10 etc. China has also made many attempts to popularize and apply recycled concrete and has implemented a series of policies and regulations, to tackle the waste concrete management issues.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of researches have been conducted on the fresh, mechanical properties and durability of recycled concrete at national and international. Many studies have shown that RCA can be used as building materials, such as graded slabs, 6 beams, 7 frame structures, 8 highway cushion material, 9 paving blocks, 10 etc. China has also made many attempts to popularize and apply recycled concrete and has implemented a series of policies and regulations, to tackle the waste concrete management issues.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, using recycled aggregate causes changes of the mechanical properties of the concrete that must be considered, for example 21,22 . By impinging in structural engineering issues through changing of the material characteristics by implementing nonstandard materials in construction concrete, considerations and calculations in view of tunnel design and structural analysis need to be carried out to guarantee the projected service lifetime of the tunnel structure 23–25 …”
Section: Introductionmentioning
confidence: 99%